2020
DOI: 10.1016/j.ijmecsci.2019.105242
|View full text |Cite
|
Sign up to set email alerts
|

Highly stretchable two-dimensional auxetic metamaterial sheets fabricated via direct-laser cutting

Abstract: We now differentiate between the requirements for new and revised submissions. You may choose to submit your manuscript as a single Word or PDF file to be used in the refereeing process. Only when your paper is at the revision stage, will you be requested to put your paper in to a 'correct format' for acceptance and provide the items required for the publication of your article. To find out more, please visit the Preparation section below. Highlights Highlights are mandatory for this journal as they help incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…This behaviour arises due to the fact that rather than rotating with respect to one another, the square units bend and stretch out-of-plane in a wave-like manner. This behaviour has previously been observed and reported in macroscale rotating square systems which are either extremely thin or in systems where the rotating mechanism has reached its fully-opened conformation [51]. Besides the loss of auxeticity, this type of deformation also results in the formation of irregularly-shaped apertures upon loading which are not directly oriented with the main plane in which the system is loaded.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This behaviour arises due to the fact that rather than rotating with respect to one another, the square units bend and stretch out-of-plane in a wave-like manner. This behaviour has previously been observed and reported in macroscale rotating square systems which are either extremely thin or in systems where the rotating mechanism has reached its fully-opened conformation [51]. Besides the loss of auxeticity, this type of deformation also results in the formation of irregularly-shaped apertures upon loading which are not directly oriented with the main plane in which the system is loaded.…”
Section: Resultssupporting
confidence: 66%
“…The work conducted in this study could potentially be used as a blueprint for the design of twodimensional nano-porous reconfigurable metamaterials. Although the base design of the rotating square geometry was used in this study, previous works on macroscale auxetic systems [46,50,51] have shown that a variety of slit perforation patterns exist which may be used to design planar nanostructures based on similar deformation modes. This could potentially open up the possibility of manufacturing nanostructured metamaterials with a wide range of aperture shapes and sizes which can be reconfigured through actuation, particularly if the slit patterning is based on a metamaterial with the potential to exhibit a large negative Poisson's ratio.…”
Section: Resultsmentioning
confidence: 99%
“…As one may observe from the plots in Figure 11, the small strain deformation behaviour of printing constraints), which are not sufficient to completely eliminate boundary effects. This edge effect has been previously observed in a range of other metamaterial geometries [37,40] and the discrepancy between the periodic and experimental models (as well as the non-periodic FE simulations) can be reduced by using a larger number of representative units in the latter systems.…”
Section: Effect Of Truss Thickness On Mechanical Propertiessupporting
confidence: 58%
“…[31,[52][53][54] The influence of the edge might be associated with constraints of the edge on the operative deformation modes, including potential shear-induced deformation. In simulation and experimental studies on the tensile behavior of tetrachiral honeycombs, [53,54] it was found that the auxeticity of the system decreases upon increasing the number of repeating units in the system. This behavior was found to be associated with the tendency of the tetrachiral systems to undergo shear deformation upon uniaxial loading, which is blocked by the edge effects at the regions where the geometry is being fixed.…”
Section: Discussionmentioning
confidence: 99%
“…MR auxetic structures have attracted many research attentions recently. [34,[48][49][50][51][52][53][54][55] Many of the applications are intended for application under in-plane compression loads, and it is important to establish a detailed understanding on the deformation process, in particular, the contact between the edges and cell walls at high strains for normal MR and MSs, which are directly relevant to the mechanical behaviors and the stability of the cell and overall sample deformation. MSs could offer opportunities to further enhance the freedom in structures design.…”
mentioning
confidence: 99%